A proposal for a theoretical methodological arrangement for when history meets fiction (TEL Tempo, Espaço e Linguagem, 2023)
This article proposes the sharing of a possible methodological theoretical arrangement, an itinerary through authors such as Luiz Costa Lima, Wolfgang Iser and Dominick LaCapra, in order to handle concepts and analytical tools that may contribute to the analysis of fictional discourse by historiography. As an arrangement, it is constructed from various permutations, the ordering of conceptual elements and the dialogue between different theories. This is one of the possible ways to scrutinize fiction, the result of a developed analysis experience, which we would like to share as an alternative contribution or guide for those and those who make fiction their source.